GNSS signal propagation through ionosphere - Lo, Wai Cho (Nanyang Technological University, 2021)
Global Navigation Satellite System (GNSS) applications such as satellite navigation, tracking, mapping, and timing have been widely used in recent years. Because of our increasing reliance on them, it is critical that we gain a better understanding of GNSS signal transmission and any jeopardizing factors that cause signal degradation. In equatorial/low-attitude areas, ionospheric scintillation is a significant cause of VHF/UHF signal degradation. Singapore scintillation data was obtained from the Septentrio PolaRxS, a GPS receiver located at 1.34◦N, 103.68◦E in the West of Singapore. First, the cause of ionospheric scintillation was discussed, as well as the theoretical explanations for the well-known diurnal, seasonal, and solar activity patterns of amplitude scintillation in equatorial/low-latitude regions. Then, from January 2019 to December 2019, Total Electron Content (TEC) scintillation data was compiled and analysed, to confirm the well-known patterns.